CONTROL REGION-mtDNA HETEROGENEITY OF KALIMANTAN FALSE GHARIAL (Tomistoma schlegelii) POPULATION: A PRELIMINARY STUDY - Hellen Kurniati (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2003)
The preliminary genetic study on Kalimantan "false gharial" from the wild was reported. Eleven tail scutes were collected from eleven individuals that originally consisting of two individuals from Kapuas River, one individual from Sentarum Lake, Jelai River, Mapam River, Perian Lake, and Lamandau River, two individuals from Barito River and three individuals from Mahakam River. PCR amplifying and sequencing 451 nucleotides in average that can be aligned at the same length of control region mitochondrial DNA. Among 11 individuals found eight polymorphic sites that consisted four haplotypes (A, B, C, and D) respectively, which is haplotype A is dominant. Based on phylogenetic tree that constructed by Tamura-Nei parameter, false gharial population in Kalimantan can be divided into two population groups; there were Central-Eastern Kalimantan population group and Western Kalimantan population group. Based on the hypothesis of landmasses separating between central-eastern Kalimantan and western Kalimantan that known as Schwaner Mountains, the genetic distance D = 1.53% was expected to be equal to 20 million years.